(untitled) (Scientific journal of the Fergana State University, 2024)
Today, in economically developed countries, the competence approach is modernizing the content of education, becoming one of the new areas of study. The basis of the new content of general education in these states is the formation and development of basic competencies of students. The progress of each society depends on how effective the education of the nationʼs youth in the national spirit is, their preparation for public life, a way of life based on national values. Therefore, over the centuries, every nation, people have formed views on the organization of the upbringing of the younger generation on the basis of their national values. As a result of the organization of the educational process on the basis of a national approach, young people acquire qualities that express in them the peculiarities of the national mentality. This article discusses aspects of the development of professional competence of future technical specialists based on multimedia tools.